The Effect of Service Quality, Store Image and Price Fairness Perception on Loyalty Through Customer Satisfaction in Coffee Shop - Fadhil Fitroh Setiawan; Unik Dwi Lestari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the effect of perceived service quality, store image and perceived price fairness on loyalty through coffee shop customer satisfaction in Tangerang district. The target sample of this study were customers of 3 coffee shops in Tangerang district. There were a total of 260 respondents who participated in this study. Data was collected using a questionnaire distributed online via google form. The data were analyzed using a partial least square-structural equation modeling (PLS-SEM) approach. The results confirmed that service quality, store image and price fairness all three have a direct and significant relationship with customer satisfaction and customer loyalty. In addition, other findings show that service quality, store image and price fairness have a significant indirect effect on customer loyalty through the mediating effect of customer satisfaction. This research provides guidance to service providers on how to increase customer satisfaction and loyalty through an emphasis on price fairness, store image and service quality. it can be suggested that if a coffee shop company wants to increase customer loyalty what it must do is attract loyal and new customers.